МОНГОЛ ХЭЛНЭЭС ЧЕХ ХЭЛЭНД, ЧЕХ ХЭЛНЭЭС МОНГОЛ ХЭЛЭНД ОРЧУУЛАГДСАН БҮТЭЭЛҮҮД - Д.Энхжаргал, (Acta Mongolica, 2015)
In this research paper we have discussed the most famous translated works from Mongolian into Czech, from Czech into Mongolian and given the researchbased information. Translated works from Mongolian into Czech and from Czech into Mongolian were found in the libraries, namely: The National Library of Mongolia, Ulaanbaatar Public Library of Natsagdorj.D, The Library of National University of Mongolia, Municipal Library of Prague. The overview of the translated and published works was done. The paper has two parts: Translated works from Mongolian into Czech and Translated works from Czech into Mongolian.